Safety beyond Sight: Handheld Metal Detectors as Diagnostic Allies in the Management of Children Suspected to have Ingested Foreign Bodies - Tomaz Krencnik; Tadej Jalsovec; Martina Klemenak; Petra Riznik; Jernej Dolinsek (Diagnostics, 2024)
Background. Foreign body (FB) ingestion remains a common cause of pediatric emergency department referrals, and the gold standard for detection is whole-digestive-tract radiographic examination. Our study explores whether handheld metal detectors (HHMD) can effectively identify the presence and location of ingested metal objects, potentially reducing the need for additional radiographic examination. Methods. We collected medical data from children with suspected metal FB ingestion who were referred to our emergency department (October 2017–March 2023), focusing on object type and correlating metal detector findings with radiographic images. Results. Data from 43 children (39.5% female; mean age: 4 y) referred to our emergency department were analyzed. Coins (32.6%), button batteries (18.6%), and hairpins (11.6%) were the most common ingested objects. Metal detectors detected the presence of FBs in 81.4% of cases (sensitivity: 89.7%; specificity: 100%). Radiographs, taken for 40 children, showed that the most common locations were the stomach (37%) and intestine (33%). The metal detector signals matched the radiography results in 69.8% of cases. According to HHMD, 34.9% of objects were accessible via endoscopy, contrasting with 51.2% via radiography (p < 0.05). Conclusion. While the findings obtained using handheld metal detectors often correlate well with radiograph findings in detecting metal FBs, for an important number of children, this confirmation is lacking, especially when determining the exact location of an object.